The Frequency Of Hematological Abnormalities in Children (Age 1 Month To 12 Years) Presenting With Sars-Cov-2 Infection At Shifa International Hospital - Muntaha, Sidra Tul; Ayaz, Hammad; Mahmood, Huma; Kulsoom, Afifa; Tayyab, Muhammad; Farooq, Arslan (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the frequency of haematological abnormalities in pediatric patients presenting with COVID-19 infection. Methods: A Cross-Sectional analytical study was conducted at the paediatric department of Shifa International Hospital Islamabad, over a period of six months from December 2021 to June 2022. A total of 325 pediatric patients of 1 month to 12 years of age who presented with symptoms of COVID-19 having positive reverse transcription polymerase chain reaction results were included in this study. Effect modifiers such as age and gender were controlled through stratification. Post-stratification Chi-square test was applied to determine the association of these effect modifiers with haematological abnormalities. A p-value equal to or less than 0.05 was considered significant. Data analysis was done using SPSS version 24.0. Results: The mean age of patients included in this study was 5.62±2.70 years. The majority were males with a male to female were 187(57.54%) and 138 (42.46%) respectively. Low WBC count was found in 58 (17.8%), leukocytosis in 20 (6.2%), thrombocytopenia in 43(13.2%), thrombocytosis in 06(1.8%), neutropenia in 69 (21.2%), lymphopenia in 17 (5.2%), lymphocytosis in 59 (18.2%), monocytopenia in 10 (3.1%), deranged fibrinogen levels in 07 (2.2%), deranged D-Dimers in 154 (47.4%) and deranged INR in 166 (51.1%) patients. Conclusion: Hematological abnormalities are common in children presenting with COVID-19 infection. Deranged INR, D-Dimers, low WBC count, thrombocytopenia and neutropenia were commonly found in haematological abnormalities in children with COVID-19 infection. Keywords: COVID-19, Hematological abnormalities, Neutropenia, SARS-COV-2 infection.